2019
DOI: 10.1016/j.ijhydene.2019.06.200
|View full text |Cite
|
Sign up to set email alerts
|

Providing significantly enhanced photocatalytic H2 generation using porous PtPdAg alloy nanoparticles on spaced TiO2 nanotubes

Abstract: In the present work we introduce a simple approach to produce porous PtPdAg alloy nanoparticles on TiO2 nanotubes by a simple combined sputtering-dewetting-dealloying process. In a first step, three individual metals (Pt, Pd and Ag) were sequentially sputter-deposited on spaced TiO2 nanotubes, followed by a thermal dewetting treatment in Ar to convert these metal layers into ternary PtPdAg alloyed particles. Dealloying was carried out by a selective chemical dissolution of Ag in piranha solution that finally g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 46 publications
0
11
0
Order By: Relevance
“…[18,[25][26][27][28][29] In spite of the large application in heterogeneous catalysis, there is however still a comparably low number of studies on nanoporous metal co-catalysts for photocatalytic applications. Nguyen et al have reported on porous Au, [30] AuPt, [31] or PtPd [32] nanoparticles produced on TiO 2 nanotubes (NTs) by chemical dealloying of dewetted-alloyed nanoparticles. These porous nanoparticles combined to TiO 2 were found to strongly enhance the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[18,[25][26][27][28][29] In spite of the large application in heterogeneous catalysis, there is however still a comparably low number of studies on nanoporous metal co-catalysts for photocatalytic applications. Nguyen et al have reported on porous Au, [30] AuPt, [31] or PtPd [32] nanoparticles produced on TiO 2 nanotubes (NTs) by chemical dealloying of dewetted-alloyed nanoparticles. These porous nanoparticles combined to TiO 2 were found to strongly enhance the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“…Nguyen et al. have reported on porous Au, AuPt, or PtPd nanoparticles produced on TiO 2 nanotubes (NTs) by chemical dealloying of dewetted‐alloyed nanoparticles. These porous nanoparticles combined to TiO 2 were found to strongly enhance the photocatalytic activity.…”
Section: Introductionmentioning
confidence: 99%
“… Most methods use 300 W Xe lamps, a much higher wattage than the ones used in the present study (maximum 54 W corresponding to the use of three lamps of 18 W lamps each) 8,17 ; Many methods have used noble metals in the composition of catalysts, making the process more costly 6,9,16 ; Most of the cases applied sacrificial agents with more α‐H atoms adjacent to the hydroxyl groups, camouflaging hydrogen production via water splitting to alcohols or mineralizing agents, which are considered more toxic and are employed in higher concentrations when compared to the 10% ethanolic solution used in the present method. …”
Section: Resultsmentioning
confidence: 93%
“…Hydrogen is a clean source of energy and it can be achieved from different renewable sources, such as catalytic reforming of acids and alcohols, [1][2][3][4] and also from catalytic hydrolysis of sodium borohydride 5 and water. [6][7][8][9][10][11][12][13][14][15][16][17] Solar energy and water are potentially the most abundant renewable energy sources available on the planet, 14,18 so their combination creates an environmentally friendly reaction mechanism for the hydrogen production. Hydrogen production by catalytic photolysis of water is considered one of the most promising technologies for producing this alternative energy source.…”
Section: Introductionmentioning
confidence: 99%
“…It follows that there is a reduction in crystallinity compared to the non-treated sample by the diminution of the peak intensity and also a broadening of the peaks indicated more amorphous materials. At XRD (Figure 1), TiO2 anatase phase peaks were observed, such as at 2θ = 25°, 38°, 48°, 54°, 55°, 63°, and rutile phase peaks at 2θ = 27°, 36°, 41°, 54.5° [4,11,[20][21][22][23][24][25]. A phase transformation from anatase to rutile was observed.…”
Section: Resultsmentioning
confidence: 99%